Energy transition toward a low-carbon economy in Malaysia: do we need a liberalizing electricity market? - Ghazali, Farahdilah; Ismon, Nur Yuhanis; Abdul Shukor, Siti Fazilah (IGI Global, 2024)
Some studies have found that liberalized electricity market led to acceleration of the development of renewable energy sector, particularly with community-based financing for local renewable projects in place. The idea of liberalization of electricity market focuses on the fair competition especially among the key players which subsequently entice more investment on infrastructures and reduce electricity tariff. Energy liberalization has dramatically enhanced monopoly utility governance, competition, innovation prospects, and the policy for environmental emissions management by creating trading mechanisms. This chapter discusses the practices of power liberalization, especially in Europe, regarding the benefits and challenges. Moreover, the chapter examines Malaysian practices in pursuing renewable energy programs to attain sustainability and energy security goals, which is also vital to support a more competitive energy sector.